(untitled) (Journal of actual problems of jurisprudence, 2023)
In the article, the author analyzes the legal norms for the compliance of the quality of meat and meat products with the current legislation of the Republic of Kazakhstan. Since the industrial development of the country’s agro-industrial complex, including the meat industry, requires new approaches to state regulation and the development of state support measures for this area. So there is a need to carry out research on a specific topic, taking into account the not entirely favorable situations in the development of the meat industry. The importance of defining tasks related to the state regulation of the country’s economy in the meat industry, as well as insufficient compliance with the legal aspects of the agricultural sector, including livestock, determined the topics and need for research. The author of the article focused on the development of relations between the legislative framework and agro-industrial complex enterprises, as well as the improvement and improvement of the mechanisms for monitoring the quality of the safety of meat products in the markets and trade enterprises of the country, where in recent years the sale of unsafe meat products, both domestic and imported production. At the same time, in most cases, manufacturers and sellers of low-quality products are not responsible and go unpunished. The analysis showed that in connection with the entry into the consumer market of a large volume and a diverse range of domestic and imported meat products, careful and quick control of their quality is required. To solve some aspects of the problem of quality, safety and conformity assessment of products, it becomes necessary to use effective methods. The author examines the process of compliance with the necessary requirements for the quality of meat and meat products in Kazakhstan. Based on the analysis of existing legislative acts, the author gives recommendations on solving legal problems of ensuring proper control of the production and sale of meat and meat products, as well as a legal assessment of state quality standards. Key words: food security, meat, meat products.